(untitled) (Research, Society and Development, 2020)
The adequate provision of basic sanitation services is an essential condition for public health and quality of life of the population. The lack or insufficiency of sanitation services coverage may cause several externalities that could harm public health and social well-being. The purpose of this study was to elaborate a health indicator through the relationship between infant mortality rate, urban population and sanitation services coverage (such as piped water, solid waste collection, water supply and sewage). This was a documentary and exploratory study that utilized multivariate analysis techniques and efficiency criteria (r², Nash-Sutcliffe and root mean square error). The area covered by the study were the municipalities of the State of Pará, divided into six geographical mesoregions. The data related to the sanitation indicators, infant mortality rate until the age of 5 and urban population were obtained through the United Nations Development Programme (UNDP) website. The results indicate that the urban population variable in households without municipal solid waste collection showed lower significance in the health indicator. It was found that association between IS and basic sanitation services (explanatory variables), overall, is statistically well explained by r² and NASH, signaling that the statistical models are appropriate and efficient. It is concluded that the reduction of infant mortality is directly proportional to sanitation coverage.